Effect of Nutrition Therapy on Ferritin in Pregnant Women with Anemia at Gamping 2 Public Health Center: Pengaruh Terapi Gizi Terhadap Feritin Pada Ibu Hamil Dengan Anemia di Puskesmas Gamping 2 - Shafriani, Nazula Rahma; Fauzia, Faurina; Wahyuntari, Evi (Jurnal Kebidanan Midwiferia, 2023)
Cases of anemia in pregnant women in Indonesia are 48.9% and have the potential to endanger the safety of mother and child. Iron deficiency will cause a decrease in ferritin levels and will cause a decrease in hemoglobin levels below normal limits. Objective: to determine the effect of nutritional therapy for 2 months on serum hemoglobin and ferritin levels in anemic pregnant women in the second trimester. Experiment with a pretest-posttest control group design approach. A sample of 2nd trimester pregnant women with anemia at the Gamping II Health Center was 44 people. The sampling technique was Simple Random Sampling, divided into 2 groups, namely the case group 22 people received nutritional counseling therapy and Fe supplements and the control group 22 people received Fe supplement therapy. Both groups will compare the results of ferritin levels before and after receiving nutritional therapy for 2 months. Data collection used a ferritin test kit, sociodemographic data, obstetric history, nutritional counseling form, Fe supplement intake form. Analysis used the Independent t-test with STATA 13. Results the average ferritin of anemic pregnant women who were given nutritional counseling therapy and Fe supplements was 62.01 ng/mL, while anemic pregnant women who received Fe supplements obtained an average of 51. 4 ng/mL. The results of the statistical test obtained p value = 0.1131, which means that there was no significant difference between the ferritin levels of the intervention group and the control group.